A SEMI-COMPENSATORY RESIDENTIAL CHOICE MODEL WITH FLEXIBLE ERROR STRUCTURE - Sigal Kaplan; Yoram Shiftan; Shlomo Bekhor (European Regional Science Association (ERSA), 2010)
Spatial choices entailing many alternatives (e.g., residence, trip destination) are typically represented by compensatory models based on utility maximization with exogenous choice set generation, which might lead to incorrect choice sets and hence to biased demand elasticity estimates. Semi-compensatory models show promise in increasing the accuracy of choice set specification by integrating choice set formation within discrete choice models. These models represent a two-stage process consisting of an elimination-based choice set formation upon satisfying criteria thresholds followed by utility-based choice. However, they are subject to simplifying assumptions that impede their application in urban planning. This paper proposes a novel semi-compensatory model that alleviates the simplifying assumptions concerning (i) the number of alternatives, (ii) the representation of choice set formation, and (iii) the error structure. The proposed semi-compensatory model represents a sequence of choice set formation based on the conjunctive heuristic with correlated thresholds, and utility-based choice accommodating alternatively nested substitution patterns across the alternatives and random taste variation across the population. The proposed model is applied to off-campus rental apartment choice of students. The population sample for model estimation consists of 1,893 residential choices from 631 students, who participated in a stated-preference web-based survey of rental apartment choice. The survey comprised a two-stage choice experiment supplemented by a questionnaire, which elicited socio-economic characteristics, attitudes and preferences. During the experiment, respondents searched an apartment dataset by a list of thresholds for pre-defined criteria and then ranked their three most preferred apartments from the resulting choice set. The survey website seamlessly recorded the chosen apartments and their respective thresholds. Results show (i) the estimated model for a realistic universal realm of 200 alternatives, (ii) the representation of correlated threshold as a function of individual characteristics, and (iii) the feasibility and importance of introducing a flexible error structure into semi-compensatory models.
Keywords: 330; residential choice; semi-compensatory; two-stage model; real-estate websites